A feasibility study to assess the design of a multi-centre randomised controlled trial of the clinical and cost-effectiveness of a caregiving intervention for people following hip fracture surgery - Smith, TO; Clark, L; Khoury, R; Man, M-S; Hanson, S; Welsh, A; Clark, A; Hopewell, S; Pfeiffer, K; Logan, PA; Crotty, M; Costa, M; et al. (British Editorial Society of Bone and Joint Surgery, 2021)
AIMS: This study aims to assess the feasibility of conducting a pragmatic, multi-centre randomised controlled trial (RCT) to test the clinical and cost-effectiveness of an informal caregiver training programme to support the recovery of people following hip fracture surgery.